OPTIMIZATION OF PLANTING MEDIA AND VARIOUS CONCENTRATIONS OF CHITOSAN AGAINST VEGETATIVE GROWTH OF KEPOK BANANA SEEDS - Helfi Gustia; Yukarie Ayu Wulandari (Jurnal AGROSAINS dan TEKNOLOGI, 2022)
Bananas are a tropical fruits commodity that is very popular with various groups of people. High nutritious bananas, contain fiber that helps smooth the metabolic system and increase the body's resistance from free radicals. The research was conducted in the BBI Lebak Bulus South Jakarta, February to April 2018. The purpose of the study was to obtain planting media and chitosan concentration and determine the effect of the interaction of planting media and optimal chitosan concentration on vegetative growth of Kepok banana seedlings. The design used was a two factorial randomized factorial pattern group design. The first factor, namely M1 (soil and manure = 1: 1) and M2 (soil, manure and cocopeat = 1: 1: 1). The second factor is the concentration of chitosan C1 (without chitosan), C2 (2 mL L water-1), C3 (4 mL L water-1), C4 (6 mL L water-1) and C5 (8 mL L water-1), repeated four times. The parameters observed were plant height, stem diameter, leaf length, leaf width, and number of leaves. The results showed a combination of M2 planting media and chitosan concentration of 8 mL L water-1 showed the highest plant height, largest stem diameter, longest leaf length, widest leaf width, and highest number of leaves. The interaction of M2 planting media and chitosan concentration of 8 mL L water-1 showed the longest leaf length, widest leaf width, and the highest number of leaves. The implementation can be done carried out in research on loam, sandy loam or sandy soil with sufficient nutrient availability and water.